Menu Close

Given-that-the-roots-of-the-equation-ax-2-bx-c-0-are-and-show-that-b-2-ac-2-where-Mr-Hans-




Question Number 214414 by ChantalYah last updated on 07/Dec/24
Given that the roots of the equation  ax^2 +bx+c=0 are α and β,   show that;  λμb^2 =ac(λ+μ)^2  where (α/β)=(λ/μ)                             Mr Hans
$$\mathrm{Given}\:\mathrm{that}\:\mathrm{the}\:\mathrm{roots}\:\mathrm{of}\:\mathrm{the}\:\mathrm{equation} \\ $$$$\mathrm{ax}^{\mathrm{2}} +\mathrm{bx}+\mathrm{c}=\mathrm{0}\:\mathrm{are}\:\alpha\:\mathrm{and}\:\beta, \\ $$$$\:\mathrm{show}\:\mathrm{that}; \\ $$$$\lambda\mu\mathrm{b}^{\mathrm{2}} =\mathrm{ac}\left(\lambda+\mu\right)^{\mathrm{2}} \:\mathrm{where}\:\frac{\alpha}{\beta}=\frac{\lambda}{\mu} \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:{Mr}\:{Hans} \\ $$
Answered by A5T last updated on 07/Dec/24
(α/β)=(λ/μ)⇒((α+β)/β)=((λ+μ)/μ)⇒(((α+β)^2 )/β^2 )=(((λ+μ)^2 )/μ^2 )  α+β=−(b/a)⇒(α+β)^2 =(b^2 /a^2 )  ⇒(b^2 /(a^2 β^2 ))=(((λ+μ)^2 )/μ^2 )⇒λμb^2 =(λ/μ)(λ+μ)^2 a^2 β^2   ⇒λμb^2 =((α(λ+μ)^2 a^2 β^2 )/β)=αβa^2 (λ+μ)^2   αβ=(c/a)⇒λμb^2 =ac(λ+μ)^2                                    ■
$$\frac{\alpha}{\beta}=\frac{\lambda}{\mu}\Rightarrow\frac{\alpha+\beta}{\beta}=\frac{\lambda+\mu}{\mu}\Rightarrow\frac{\left(\alpha+\beta\right)^{\mathrm{2}} }{\beta^{\mathrm{2}} }=\frac{\left(\lambda+\mu\right)^{\mathrm{2}} }{\mu^{\mathrm{2}} } \\ $$$$\alpha+\beta=−\frac{{b}}{{a}}\Rightarrow\left(\alpha+\beta\right)^{\mathrm{2}} =\frac{{b}^{\mathrm{2}} }{{a}^{\mathrm{2}} } \\ $$$$\Rightarrow\frac{{b}^{\mathrm{2}} }{{a}^{\mathrm{2}} \beta^{\mathrm{2}} }=\frac{\left(\lambda+\mu\right)^{\mathrm{2}} }{\mu^{\mathrm{2}} }\Rightarrow\lambda\mu{b}^{\mathrm{2}} =\frac{\lambda}{\mu}\left(\lambda+\mu\right)^{\mathrm{2}} {a}^{\mathrm{2}} \beta^{\mathrm{2}} \\ $$$$\Rightarrow\lambda\mu{b}^{\mathrm{2}} =\frac{\alpha\left(\lambda+\mu\right)^{\mathrm{2}} {a}^{\mathrm{2}} \beta^{\mathrm{2}} }{\beta}=\alpha\beta{a}^{\mathrm{2}} \left(\lambda+\mu\right)^{\mathrm{2}} \\ $$$$\alpha\beta=\frac{{c}}{{a}}\Rightarrow\lambda\mu{b}^{\mathrm{2}} ={ac}\left(\lambda+\mu\right)^{\mathrm{2}} \:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\blacksquare \\ $$

Leave a Reply

Your email address will not be published. Required fields are marked *